Analysis of Adolescent Reproductive Health Risk Factors in Purwakarta Regency, Indonesia - Khotimah, Khusnul (HM Publisher, 2024)
Adolescent reproductive health is an important issue in Indonesia. This study aims to analyze risk factors for adolescent reproductive health in Purwakarta Regency, Indonesia. This research used a cross-sectional survey method involving 400 teenagers aged 15-24 years. Data was collected through questionnaires. Data analysis used the Chi-square test. The research results show that risk factors for adolescent reproductive health in Purwakarta Regency include: Low adolescent knowledge about reproductive health (OR: 2.17; 95% CI: 1.45-3.24); Risky sexual behavior, such as having had premarital sexual relations (OR: 2.88; 95% CI: 1.99-4.19); Unsafe use of contraceptives, such as not using contraceptives at all (OR: 2.87; 95% CI: 1.99-4.19); Lack of adolescent access to reproductive health services (OR: 2.67; 95% CI: 1.87-3.83). The conclusion of this study shows that efforts need to be made to increase teenagers' knowledge about reproductive health, reduce risky sexual behavior, increase the use of safe contraceptives, and increase teenagers' access to reproductive health services.